Analisis Spasial Kerapatan Vegetasi di Kabupaten Tabanan - Luh Gede Sri Utami; Dwipayana, Made; Sumadyanti, Umi Varica; Mardiana, Oriza (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze vegetation density in Tabanan Regency spatially using the NDVI (Normalized Difference Vegetation Index) method derived from Landsat 8 satellite imagery. The analysis process was carried out by processing band 4 (Red) and band 5 (NIR) to generate NDVI values, which were then classified into six vegetation density categories: non-vegetated, very sparse, sparse, moderate, dense, and very dense. The results showed that vegetation in the very dense category dominates most areas, particularly in highland sub-districts such as Pupuan, Penebel, and Selemadeg Barat. Conversely, lowland areas such as Kediri, Tabanan, and Marga showed lower vegetation density due to intensive human activities, such as settlements and agriculture. This study emphasizes the importance of protecting densely vegetated areas as conservation zones and highlights the need for reforestation and proper spatial planning efforts to maintain ecosystem balance and ensure environmental sustainability in Tabanan Regency.